Photoluminescence study of Zinc oxide (ZnO) nanostructured by sol-gel immersed method / Nor Iyazi Nasruddin - Nasruddin, Nor Iyazi (2010)
Nanostructured Zinc oxide (ZnO) were grown on silicon (Si) substrates through sol-gel immersed method and spin-coating technique with presence of gold as catalyst. ZnO then were annealed at temperature of 400°C, 500°C and 600°C and it found that annealing temperature had improved the crystalline structure of ZnO. The ZnO nanostructures were characterized using photoluminescence (PL) spectrofluorometer and X-ray diffraction (XRD) for morphology and optical properties study.